Disseminated TB in Immunocompetent Individual: Case Series - V, Dr. Latha; Swamy, Dr Sumedha; TR, Dr. Mamatha; Singh, Dr Virender (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Disseminated tuberculosis (dTB) is a rare disease, affects any organ system and presents mainly in immunocompromised populations. The typical presentation is non-specific, posing a challenge for diagnosis. Case series Report: This case series of 4 patients an immunocompetent patients presenting with varied signs and symptoms of disseminated TB. Our case series mainly explains how disseminated tuberculosis presents with subtle symptoms and also diagnostic clues which help in day-to-day clinical practice to pick up the diagnosis of disseminated tuberculosis. Discussion: This case series stands to acknowledge the fact of the presence of disseminated tuberculosis in immunocompetent patients and point out difficulties of diagnosis and the need for physicians to maintain a broad differential including disseminated TB as a possibility from the beginning of assessment. Physicians should be aware of predisposing factors of disseminated TB in patients presenting with non-specific symptoms. They should also acknowledge that TB may present atypically in patients with minimal predisposing factors, rendering the need to further investigate abnormal CXR images despite lab results inconsistent with TB. Conclusion: Disseminated tuberculosis although a rare disease with varying signs and symptoms, but common in immunocompetent individuals. Hence, a patient diagnosed with one site tuberculosis and immunocompetent patients should also be worked up for disseminated tuberculosis.